Discovery of novel 5‐methyl‐1H‐pyrazole derivatives as potential antiprostate cancer agents: Design, synthesis, molecular modeling, and biological evaluation. (1st March 2018) - Zhang, Daoguang; Asnake, Solomon; Zhang, Jingya; Olsson, Per‐Erik; Zhao, Guisen
Abstract : Androgen receptor (AR) signaling functions as a core driving force for the progression of prostate cancer (PCa), and AR has been proved to be an effective therapeutic target even for castration‐resistant prostate cancer (CRPC). Herein, structural modification via a fragments splicing strategy was performed based on two lead compoundsT3 and10e, leading to the discovery of a series of 5‐methyl‐1 H ‐pyrazole derivatives. AR reporter gene assay revealed compoundsA13 andA14 as potent AR antagonists. Some of the compounds in this series inhibited growth of PCa LNCaP cells more efficiently than enzalutamide.A13 andA14 also showed improved metabolic stability compared with10e in human liver microsomes. Abstract : Structure optimization via a fragments splicing strategy led to the discovery of a series of 5‐methyl‐1 H ‐pyrazole derivatives. Part of the compounds showed strong growth inhibition in prostate cancer LNCaP cells. AR luciferase reporter gene assay revealed compoundsA13 andA14 as potent AR antagonists.